2021
DOI: 10.1002/clt2.12076
|View full text |Cite
|
Sign up to set email alerts
|

Development of childhood asthma prediction models using machine learning approaches

Abstract: Background: Respiratory symptoms are common in early life and often transient. It is difficult to identify in which children these will persist and result in asthma.Machine learning (ML) approaches have the potential for better predictive performance and generalisability over existing childhood asthma prediction models. This study applied ML approaches to predict school-age asthma (age 10) in early life (Childhood Asthma Prediction in Early life, CAPE model) and at preschool age (Childhood Asthma Prediction at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…In addition, it facilitates the clinicians in patient management. Multiple studies have developed novel models to predict clinical outcomes of asthma [30][31][32]. In this study, we focused on the key role of epigenetics (methylation) in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it facilitates the clinicians in patient management. Multiple studies have developed novel models to predict clinical outcomes of asthma [30][31][32]. In this study, we focused on the key role of epigenetics (methylation) in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64] For example, SHAP was recently implemented to describe the contribution of features selected for inclusion in asthma prediction models. 65 These analytical methods calculate how each input feature contributes to each prediction, providing detailed insights into the learning patterns of the AI model.…”
Section: Explainabilitymentioning
confidence: 99%
“…The urgent need for explainability has accelerated methodological innovations to “open the black box.” Relevant examples are SHAP (SHapley Additive exPlanations), LIME (Local Interpretable Model‐agnostic Explanations), and CAM (Class Activation Maps) 62–64 . For example, SHAP was recently implemented to describe the contribution of features selected for inclusion in asthma prediction models 65 . These analytical methods calculate how each input feature contributes to each prediction, providing detailed insights into the learning patterns of the AI model.…”
Section: Challenges and Pitfalls For Ai Application In Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, increasing evidence demonstrates that bronchiolitis is a heterogeneous disease and that a viral trigger may be one of the key exposures and part of the underlying pathobiology, very important in identifying endotypes ( 2 , 10 , 11 ). Although the clinical features of bronchiolitis attributed to different viruses are usually indistinguishable, the recently recognized bronchiolitis profiles are associated with various risks for recurrent wheeze and asthma, some differences in disease severity, and, potentially, different therapeutic responses to systemic corticosteroids ( 10 13 ). For example, it has been shown that human rhinovirus (HRV)-associated bronchiolitis can result in shorter hospitalization times than bronchiolitis caused by the respiratory syncytial virus (RSV); however, the evidence around associations between virus type and severity is still unclear ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%